Integritas Pendidik Profesional dalam Tinjauan Al-Qur’an - Tarmizi Ninoersy (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2015)
Educators, in the whole education processes, are one of the essential factors in directing pedagogical and characteristic activities to achieve educational goals. To this end, their professionalism are supposed to accommodate students’ necessities in various aspects, such as spiritual, intellectual, morality, ethics as well as their basic needs. Educators are also called for to understand professional ethics in performing their duties. Furthermore, professional educators, in person, must have possessed quality and character integrity with which they will gain potential and ability to illuminate and demonstrate authority and honesty. Focusing on professional educators’ integrity, this journal highlights all issues regarding the professionalism degradation. From the results of observation and community perceptions, it was indicated that educators’ professionalism has brought about some problems, either in input aspect, distribution, academic quality, scientific activities or their feasibility. The emergence of this problem indicates that educators, in performing their duties, were not able to show a reserved integrity. For this reason, in this journal, the writer analyses professional educators integrity from Quranic perspective as an attempt to solve the preceding problems and as comprehensive scientific development of Quranic terminologies about educators’ professionalism integrities